(untitled) (Biological Sciences - PJSIR, 2004)
Phytic acid, present in cereals and grain legumes, is determined by several procedures involving different principles. The most common and practical is the one with extraction of phytic acid with acid solution, reaction with iron solution of known concentration and back determination of the free iron. Back determination is carried out using the 2,2-bipyridine reagent. This, besides being expensive, has several other demerits. The determination is time bound, measurement is possible in only a limited range of concentrations and the concentration dependency of the procedure is relatively low. The procedure was modified by replacing the 2,2-bipyridine procedure with potassium thiocyanate after making the necessary procedural adjustments. The curve with the pyridine procedure becomes parallel to X-axis at concentrations beyond 30µg/ml of P-Phytate; whereas that of the KSCN procedure remains straight line, indicating its applicability in even higher concentration ranges. The procedure was validated using recovery studies.